The Breastfeeding Readiness Score In Bangka Belitung Province - Damayani, Ayi Diah; Permata, Tesza Rezky; Lubis, Astri Yulia Sari; Aminin, Fidyah (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: Exclusive breastfeeding in Indonesia is still a challenge in several regions. Socialization and provision of information from various sides have not had a direct impact. Many factors influence the success of breastfeeding, one of which is the mother's belief in providing breast milk. The breastfeeding readiness scale is one of the tools to assess the readiness of mothers in providing exclusive breastfeeding. Purpose: This study aims to determine the effectiveness of the breastfeeding readiness scale in Bangka Belitung Province. Method: The study was cross-sectional. The number of respondents involved was 185 respondents who met the inclusion criteria, namely having children aged 0-6 months. The analysis was carried out univariately and bivariately using SPSS. Results: of the 185 respondents, 67% of them had children> 1, most mothers were in the reproductive age of 20-35 years, namely 78%, with an average of having further education of 57.3%. The majority of mothers did not work at 88.6%, 65% of mothers had experience of exclusive breastfeeding. Of the 185 mothers, 70% of them still exclusively breastfeed their babies, and the scale of readiness of breastfeeding mothers mostly has a very high score of 53%, but there are still mothers who have a very low score of 5 people. There is a relationship between parity (p-value 0,0036), previous breastfeeding experience (p-value < 0,001) and exclusive breastfeeding (p value <0,000) with the scale of readiness to breastfeed. There is no relationship between education, age, occupation and type of delivery with the scale of readiness to breastfeed. Conclusion: The scale of readiness to breastfeed can effectively be used as a detection tool to assess the success of breastfeeding mothers. There is a need to develop a breastfeeding readiness scale in the form of an application so that it is easy for mothers and health workers to use.